Acute motor neuropathy after intrathecal treatment with methotrexate: A case report - Pisani, Francesco; Scarano, Angela (Journal of Pediatric Neurology, 2007)
Intrathecal therapy with methotrexate and cytosine-arabinoside is a therapeutic strategy for maintaining remission in patients with acute lymphoblastic leukemia, that is associated with neurological side effects are described. We report a 4-year-old girl who became tetraplegic after the last dose of intrathecal therapy. Cerebrospinal fluid showed elevated protein level and nerve conduction study revealed a motor neuronopathy. Spine magnetic resonance imaging revealed gadolinium enhancement of the anterior roots of the cauda equina. We describe a myelopathy confined to the anterior horns and anterior spinal nerve roots without sensory involvement caused by intrathecal methotrexate. The pathogenesis of this selective involvement remains uncertain.
Keywords: Intrathecal methotrexate; acute lymphocytic leukemia; motor neuronopathy; ventral polyradiculopathy